CFD Simulation of Flame Characteristics Resulting from Volatile Matter Combustion of Various Biomass Pellets - Ramavi Akbar Akhsanul Fitrah; Ratna Dewi Kusumaningtyas; Dwi Widjanarko; Catur Rini Widyastuti; Muslikhin Hidayat; Muhammad Aziz (Advance Sustainable Science Engineering and Technology, 2026)
While biomass is a promising carbon-neutral alternative to coal, the specific volatile matter (VM) flame characteristics of diverse biomass pellets, particularly water hyacinth, remain under-researched. This study uses a numerical CFD approach (Ansys Fluent) to investigate how varying VM fractions influence flame structure in a 2D planar slice of the furnace block (25 cm width). Simulations employed the SST k–ω turbulence and Eddy dissipation model to capture mixing-limited chemical reactions. Boundary conditions were based on experimental configurations using a 0.05 m/s air inlet velocity. Results using CO-based flame-tip markers revealed that water hyacinth (VM: 63.5 wt%) produced a peak temperature of ~1,400°C at 75 cm above the fuel, while rice husk and bagasse (VM: 59–77 wt%) exhibited longer, more intense hot plumes compared to the localized heat profile of coal. These findings demonstrate that biomass generates more dispersed combustion zones, aiding in furnace hot-spot prevention and air control optimization. A limitation of this study is that findings are based solely on numerical simulations without direct experimental validation, although the model replicates physical furnace configurations. These results provide a foundation for developing sustainable biomass–coal co-firing technologies.